PROFIL KEPRIBADIAN PESERTA DIDIK DI SMP SEMEN PADANG - Wendra, Apriyus - (Bimbingan dan Konseling, 2014)
Learners who have a healthy personality can adapt well to the environment so as to fulfillthe needs with the demands (norms) environment, not all students are able to show a healthypersonality, among them there are also displays an unhealthy personality. This study aims todetermine the characteristics of a healthy personality profile of students in junior Semen Padang.This research is descriptive quantitative. The study population was all students of SMP SemenPadang. The sampling technique is stratified random sampling, samples are taken from 84 studentswho are at different grade levels. The source of data is the primary data. The instrument used wasa questionnaire, while the data used for the analysis of the percentage formula. Results of researchconducted on the personality profile in junior Semen Padang, can generally be categorized ashealthy. These results indicate that the majority of learners in junior Semen Padang has a healthypersonality. Based on the research results suggested: (1) Learners, could further enhance thedisplay of healthy personality, so it can adapt to the environment so as to fulfill the needs with thedemands (norms) environment. (2) Teachers BK, as an input to develop BK service program thatfits the needs of learners, especially in providing services related to personality BK. (3)Researchers further, be used as guidelines for research related to personality issues.